2015
DOI: 10.1007/s10995-015-1715-0
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of a Mobile Phone-Based Case Management Intervention to Retain Mothers and Infants from an Option B+ Program in Postpartum HIV Care

Abstract: Objective To assess the acceptability and feasibility of a cell-phone based case manager intervention targeting HIV-infected pregnant women on highly-active antiretroviral therapy (HAART). Methods Pregnant women ≥36 weeks gestation attending antenatal care and receiving HAART through the Option B+ program at a primary care clinic in South Africa were enrolled into a prospective pilot intervention to receive text messages and telephone calls from a case manager through six weeks postpartum. Acceptability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 14 publications
(15 reference statements)
2
65
0
Order By: Relevance
“…These cited theories include Information, Motivation and Behavioral (IMB) Skills Model [2326], Theory of Planned Behavior [27], and Motivational Interviewing [28]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These cited theories include Information, Motivation and Behavioral (IMB) Skills Model [2326], Theory of Planned Behavior [27], and Motivational Interviewing [28]. …”
Section: Resultsmentioning
confidence: 99%
“…Most of the theory-driven eHealth interventions (k = 19) were efficacious (74%, k = 14) for improving only medication adherence [32, 33, 35, 37, 38]; both medication adherence and virologic suppression [29, 30]; or care retention [26, 31]. Half (k = 7) of these efficacious, theory-based eHealth interventions were US-based [32] [33] [24, 30, 31, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to control, each of the interventions significantly increased retention in follow-up, although there were no significant differences between interventions. A similar pilot study from South Africa evaluated an SMS-and phone call-based EID intervention from a case manager both before and after pregnant women delivered [22]. In this study, 50 prospectively identified women were compared with 50 retrospectively identified controls.…”
Section: Linkage To and Retention In Carementioning
confidence: 99%